"I did not know what to expect": Music as a means to achieving work-life balance. (July 2021) - Joseph, Dawn
Work–life balance has become a buzzword in many corporate settings. This study situates itself at a higher education institute in Melbourne (Australia) where African music (singing and drumming) was used as a lever for faculty staff to "break from work" and "learn about a new music and culture". Drawing on email communication, questionnaire data, and anecdotal feedback, a phenomenological approach was adopted to explore the benefits, challenges, and opportunities staff experienced as a recreational group music activity. Data were analyzed using interpretative phenomenological analysis as a tool. Two overarching themes emerged (group participation and learning, and challenges) and are discussed in the findings. The workshops proved successful and are worthy to be replicated in other places and spaces. Further research is needed to gain insight into whether regular music workshops can influence work–life balance and professional learning for staff.